PENGGUNAAN MEDIA VIDEO ANIMASI DALAM PEMBELAJARAN IPAS TENTANG SISTEM PENCERNAAN MANUSIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDI OEPURA 3 - Maria Titiana Atu Hayon; Antonius Suban Hali; Kurniayu Triastuti R.A. Ratu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is a classroom action research study aimed at improving the learning process and outcomes through the use of animated video media in the science subject of the human digestive system in class VB SDI Oepura 3. Initial problems identified were low student learning outcomes and a lack of student engagement due to the limited use of media, resulting in students' lack of interest and difficulty understanding the material. Based on these conditions, learning innovations were needed to increase student interest and understanding. The study was conducted in two cycles, encompassing planning, implementation, observation, and reflection. Twenty students participated in the 2025/2026 academic year. Data collection methods included tests and non-tests. Pretests and posttests were used to measure learning outcomes, while observations were used to assess learning activities. The results showed an increase in student learning completion. Initially, only 30%, or 6 students, completed the task. In the first cycle, this increased to 60%, or 12 students, and in the second cycle, it reached 85%, or 17 students. These results indicate that animated video media is effective in improving learning outcomes and student engagement.